Analisis Program “Parade On Air” KISS FM Medan Dalam Meningkatkan Minat Pendengar Band Lokal Medan - Rafli Aldian Akbar Nasution; Nurhasanah Nasution (Yayasan Haiah Nusratul Islam, Indonesia, 2024)
One of the oldest mass media is radio. The great power of this media comes from its characteristics that are different from other mass media.Radio does not require complex delivery methods because it is direct. KISS FM is one of the first private radios in Medan City to survive in the fierce competition of broadcast media such as television and the internet.Despite being fifty years old, KISS FM still has a strong spirit and remains loyal to the youth demographic.This research method uses qualitative research methods. Qualitative research typically uses interviews and observations, but may also use case studies, surveys, document analysis, and ethnographic, action, and narrative research, phenomenology, and enforcement researchEvery Friday, Parade on Air is broadcast in the afternoon by KISS FM and aims to support local Medan bands with the tagline